Existence and relaxation results for nonlinear evolution inclusions revisited. (1995) - Migórski, S.
Abstract : In this paper we confirm the validity of some recent results of Hu, Lakshmikantham, Papageorgiou [4] and Papageorgiou [13] concerning the existence and relaxation for nonlinear evolution inclusions. We fill a gap in the proofs of these results due to the use of incorrect Nagy's compactness embedding theorem.